Foreign Ownership Control and the Bilateral Investment Treaties in South Asian Countries - Mohammad Hossain; Haitham Mohammed (Lex Publica, 2023)
Abstract. In absence of any global treaty, the Bilateral Investment Treaties (BITs) are playing an important role of regulating foreign investments in the host countries. According to the United Nations Conference on Trade and Development, there are 2361 bilateral investment treaties are in force and like other members of the World Trade Organization Bangladesh also signed bilateral investment treaties to facilitate trade. The primary purpose of economic globalization is the economic development of the developing and least-developed countries as well as to facilitate benefits of the home states. Bangladesh foreign investment laws and bilateral investment treaties mainly protects foreign investors, however, neither of them has any specific provision of controlling foreign ownership. This paper addresses two questions: (a) Do the bilateral investment treaties of Bangladesh allow the host state to control foreign ownership? (b) Should the foreign ownership be controlled during the entry of foreign direct investment in Bangladesh? Using doctrinal research method, we critically analyzed 15 bilateral investment treaties to explore whether there is any reference of controlling foreign ownership in Bangladesh. We find that the existing Bangladesh bilateral investment treaties has provisions to promote and protect foreign investments but has no reference of controlling foreign ownership, therefore, the government of Bangladesh should consider this important factor while signing any future bilateral investment treaties. Abstrak. Dalam ketiadaan perjanjian global tertentu, Perjanjian Investasi Bilateral memainkan peran penting dalam mengatur investasi asing di negara tuan rumah. Menurut Konferensi Perserikatan Bangsa-Bangsa tentang Perdagangan dan Pembangunan, saat ini terdapat 2361 perjanjian investasi bilateral yang berlaku, dan seperti anggota lain Organisasi Perdagangan Dunia, Bangladesh juga telah menandatangani perjanjian investasi bilateral untuk memfasilitasi perdagangan. Tujuan utama dari globalisasi ekonomi adalah pengembangan ekonomi bagi negara-negara berkembang dan yang paling kurang berkembang serta memfasilitasi manfaat bagi negara asal. Hukum investasi asing dan perjanjian investasi bilateral Bangladesh pada dasarnya melindungi investor asing, namun keduanya tidak memiliki ketentuan khusus untuk mengendalikan kepemilikan asing. Makalah ini mengangkat dua pertanyaan: (a) Apakah perjanjian investasi bilateral Bangladesh memungkinkan negara tuan rumah mengendalikan kepemilikan asing? (b) Haruskah kepemilikan asing dikendalikan selama masuknya investasi langsung asing di Bangladesh? Dengan menggunakan metode penelitian doktrinal, kami secara kritis menganalisis 15 perjanjian investasi bilateral untuk mengeksplorasi apakah terdapat referensi pengendalian kepemilikan asing di Bangladesh. Kami menemukan bahwa perjanjian investasi bilateral Bangladesh yang ada memiliki ketentuan untuk mempromosikan dan melindungi investasi asing tetapi tidak memiliki referensi pengendalian kepemilikan asing. Oleh karena itu, pemerintah Bangladesh sebaiknya mempertimbangkan faktor penting ini saat menandatangani perjanjian investasi bilateral di masa depan. Kata kunci: Perjanjian investasi bilateral, Pengendalian kepemilikan asing, Investasi langsung asing, Perlindungan hukum, Organisasi Perdagangan Dunia